Intervensi Continuous Improvement Rawat Jalan Rumah Sakit Haji Jakarta - Ariotejo, Teguh (UI Scholars Hub, 2017)
The process of general patient care in the outpatient installation of Haji Hospital Jakarta when viewed from the outpatient mobility flow since registration until the patient came home seen the flow that makes the patient walk back and forth to the cashier or to the supporting room service (laboratory and radiology). This is of course a waste of time and the movement of patients. Therefore, continuous improvement is needed in the effort to improve the quality and efficiency of service to the patient in the outpatient installation of Jakarta Hajj Hospital.